Luteolin enhances oxidative stress tolerance via the daf-16 pathway in the nematode Caenorhabditis elegans - Yamamoto, Ryoko; Takahashi, Eriko; Harada, Maho; Sawahata, Izumi; Nishizuka, Makoto (Food Science and Technology Research, 2024)
Luteolin, widely present in plants, has various physiological functions. Here, we aimed to investigate whether luteolin affects lifespan and oxidative stress tolerance using Caenorhabditis elegans. Luteolin had no effect on the lifespan of wild-type N2 worms under normal conditions. In contrast, luteolin prolonged the lifespan of N2 worms under oxidative stress, suggesting that luteolin enhances oxidative stress tolerance. Luteolin upregulated the expression of gst-4, sod-1, sod-2, sod-3, and ctl-3 in N2 worms under oxidative stress conditions. The expression of these genes was regulated by DAF-16. Prolongation of lifespan and induction of gene expression by luteolin under oxidative stress conditions were not seen in daf-16 (mu86) mutants. These results suggest that the enhancement of oxidative stress tolerance by luteolin was mediated by the daf-16 pathway in C. elegans.